Assessing development intensity and ecological risk of islands on the eastern coast of China: Promotion of refined classification management. (1st December 2020) - He, Cong-Ying; Wang, Jian-Qing; Yan, Xiao-Jun; Meng, Kuan-Hong
Abstract: The development of the marine economy has become a national strategy for China, and islands have become a hot spot for marine economic development. In addition, residents of islands are involved in social and economic activities in coastal zones. In this study, we established an evaluation system for the intensity of island development under the framework of extenics theory. In order to examine the overall development level of the islands in specific areas, we calculated the regional development index. Threat and intensity indices were designed to calculate the pressure that human exploitation puts on island ecosystems, and therefore demonstrate the credibility of the intensity of island development. Forty-six islands along eastern coast of China were chosen for study. The results showed that the numbers of the islands with very low, low, medium, and high intensities of development were 6, 8, 15, and 17, respectively. Among them, Yuhuan Island had the highest intensity of development. The ecological risk indices collected from four types of islands had significant differences, which were very consistent with the results of development intensity. The results of regional island development index showed that Sanmen Gulf was the most developed island region, Yueqing Gulf second and Taizhou Gulf third respectively, while Xiangshan Harbor was a location with very low island development. Finally, based on the demarcation result of the level of development intensity, refined classification management strategies were then proposed. This study provided a basis for island planning and management to ensure the sustainable and healthy development of island resources and avoided damage to resources and a loss of assets. Graphical abstract: Image 1 Highlights: The factors that affect the intensity of island development are complex and diverse. A combined assessment model is established for the intensity of island development. Regional island development indices (RIDI) are calculated in four gulfs. Refined classification management strategies are proposed. Yuhuan Island has the highest development intensity.